Relationship between Mindfulness and Interest in Learning among Cognition of SMK Metta Maitreya Pekanbaru Students - Handomo Lesmana (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2022)
The study used stratified random sampling of 131 students from 195 SMK students. The research design was a quantitative correlational approach, associative hypothesis, and cross-sectional survey method. The instrument for collecting data was a closed questionnaire via Google Forms. The questionnaire results were tested through instrument testing of validity and reliability, classical assumptions, correlation analysis, and simple and multiple regression with a level of = 0.05. The results of data analysis: (1) There is a low, positive, significant relationship between mindfulness and cognition, the correlation value is 0.271, the coefficient of determination is 0.073, and the effective contribution is 5.420%; (2) There is a low, positive, significant relationship between interest in learning and cognition, the correlation value is 0.270, the coefficient of determination is 0.073, and the effective contribution is 5.346%; (3) There is a low, positive, significant relationship between mindfulness and interest in learning simultaneously with cognition, the correlation value is 0.328, the coefficient of determination is 0.108, and the total effective contribution is 10.766%. The study's results conclude that students' cognition can be improved through increased mindfulness and student interest in learning, either partially or simultaneously.